Evaluación de los riesgos psicosociales presentes en el Colegio Infantil Futuros Sabios y su contribución a los costos de no calidad empresarial (2018)
Currently psychosocial risks are related to work in an unimaginable way, the negative effects on the health of workers and business organizations that are increasingly involved in these psychosocial risks. The continuous changes, although small, affect the workplaces of all of Colombia, which generates daily challenges for health and safety at work. Keep in mind that many of these changes offer opportunities in development, however when employers or organizations try to achieve these opportunities in order to compete and stand out among other companies most of the time they do it in an incorrect way and it is there where the psychosocial risk factors are inclined to the negative part by the poor organization of work increasing the psychosocial risks, which will produce illnesses to the workers hindering their daily work. If employers do not avoid exposing their workers to psychosocial risks, they will have stress, resulting in poor performance and in the long term they will have serious health problems. Employers are obliged to reduce psychosocial risks in terms of occupational safety and health; However, many of the organizations have a misperception about intervening or carrying out evaluations to validate the level of psychosocial risks. Many think that investing in evaluations is losing money, without knowing that these risks are damaging them financially. When employees are affected by these psychosocial risks, companies are practically directly affected by increases in costs (doctors, insurance, replacement personnel). The companies are hit by the affectation of the production, the high levels of absenteeism and in many cases the rotation of the personnel. The purpose of the present work of degree is the identification and evaluation of the psychosocial risks and how they contribute to the costs within the future wise RIESGOS PSICOSOCIALES Y SU CONTRIBUCION A LOS COSTOS 14 children's school. The fulfillment of these objectives was carried out with the first phase, which was the identification and evaluation of the psychosocial risk factors with the implementation of the intralaboral psycho-social risk battery form A. In the second phase, the most relevant risk factors were obtained and, as they affected the development of the employees' daily activities, all the factors were detailed and explained in an appropriate manner. In the third phase, the non quality and loss costs that are being generated due to the psychosocial risks that are present within the educational institution were calculated. In the last phase and taking into account the results, improvements were proposed, conclusions of the research were established